SPE California Regional Meeting 1990
DOI: 10.2118/20070-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Bubble Flow in Heavy Oil Reservoirs

Abstract: SPE Members Abstract A new mechanism of fluid flow in solution-gas drive heavy oil reservoirs is identified through experimental studies. This paper presents experimental results in order to verify previous hypothesis on fluid flow in heavy oil reservoirs in Canada. It has been postulated that solution-gas drive in these reservoirs involves simultaneous flow of gas and oil. However, gas remains in tiny droplets under reservoir conditions. A new mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Smith (1988) was the first to develop an apparent in-situ oil viscosity equation for two-phase foamy oil. Later Islam and Chakma (1990) calculated a mixture viscosity to account for microbubbles in the oil using the volume fraction of oil and the single-phase viscosities of the gas and oil. Poon and Kisman (1991) indicated that foamy oil exhibits non-Newtonian flow, and shear thickening effects account for the low viscosity far from the wellbore where the shear rates are low.…”
Section: Introductionmentioning
confidence: 99%
“…Smith (1988) was the first to develop an apparent in-situ oil viscosity equation for two-phase foamy oil. Later Islam and Chakma (1990) calculated a mixture viscosity to account for microbubbles in the oil using the volume fraction of oil and the single-phase viscosities of the gas and oil. Poon and Kisman (1991) indicated that foamy oil exhibits non-Newtonian flow, and shear thickening effects account for the low viscosity far from the wellbore where the shear rates are low.…”
Section: Introductionmentioning
confidence: 99%
“…The bubble size seems to be smaller (Islam, 1990) and the rate of produced bubbles higher (Kennedy & Olson, 1952, Hunt&Berry, 1956, Moulu, 1989) if the supersaturation is higher. Since both nucleation and diffusion of dissolved gas are driven by supersaturation, this might indicate that when the supersaturation exceeds some limit value, the nucleation rate increases stronger than the diffusion.…”
Section: Supersaturation and Bubble Creationmentioning
confidence: 97%
“…The mechanics of bubble flow in heavy oil reservoirs is discussed by Islam (1990), who performs experiments on the flow of a foamy oil in capillary tubes and core flow experiments. Although supersaturation is not directly discussed in this paper, Islam finds that at higher pressure decline rates, smaller bubbles are found and higher recoveries.…”
Section: -1omentioning
confidence: 99%
“…This reduction in the asphaltene content in oil reduces the live-oil viscosity (Claridge 1994). However, different experimental studies suggest either an increase or a decrease in the apparent oil viscosity in the presence of bubbles (Bora 1998;Fisher et al 1999;Goodarzi et al 2005;Islam and Chakma 1990;Albartamani 2000). Thus, the effect of dispersed bubbles on heavy-oil flow properties in porous media is still debatable.…”
Section: Introductionmentioning
confidence: 99%